Efficacy and safety of lanreotide in postoperative dumping syndrome: A Phase II randomised and placebo‐controlled study. Issue 8 (1st October 2019) - Wauters, Lucas; Arts, Joris; Caenepeel, Philip; Holvoet, Lieselot; Tack, Jan; Bisschops, Raf; Vanuytsel, Tim
Abstract : Background: Data on the efficacy and safety of the long‐acting somatostatin analogue lanreotide (LAN) for postoperative dumping syndrome are lacking. Objective: We performed a double‐blind, randomised and placebo‐controlled crossover study of LAN Autogel® 90 mg in postoperative dumping. Methods: Adults with a positive prolonged oral glucose tolerance test or spontaneous hypoglycaemia and total dumping score (DS) ≥ 10 despite dietary measures were treated with three monthly injections of LAN or placebo in a randomised crossover fashion with an eight‐week wash‐out period. Primary outcome was the effect of LAN on total DS versus placebo. Secondary outcomes were the effect on early and late DS, treatment assessment, quality of life and safety. Results: Of 24 included patients (66.7% female; age 49.1 ± 2.1 years), 12 were randomised to LAN first. Pooled DS after three injections were lower compared to baseline after LAN (median=14 (interquartile range (IQR) 11.5–23) vs. median = 22 (IQR 16–27); p  = 0.03) but not placebo (median = 20 (IQR 15–27) vs. median = 23 (IQR 13–29); p  = 0.15). Improvement of early (median = 7.5 (IQR 4.5–13) vs. median = 12 (IQR 9–16); p  = 0.03) but not late (median = 7 (IQR 6–10.3) vs. median = 9 (IQR 6–13); p  = 0.26) DS was seen. Overall treatment assessment correlated with change in DS ( r  = –0.69, p  = 0.004). Symptom improvement was not associated with changes in quality of life. Of the 81 reported adverse events, 44 occurred on LAN compared to 37 on placebo ( p  > 0.05), with seven serious adverse events on LAN. Conclusions: LAN is effective for treating early postoperative dumping symptoms, although side effects are common and quality of life is not significantly affected.